Strategies for Gully Stabilization and Highland Protection in Chinese Loess Plateau - Liu, Wanfeng; Zhang, Huyuan; Zhu, Jianghong; Hu, Aiping (Frontiers in Earth Science, 2022)
Loess tablelands are large-scale platforms with flat top surfaces in the center of Chinese Loess Plateau, such as Dongzhiyuan, which is a ∼900 km2 loess stratum, with the thickness larger than 200 m. The break of loess tablelands is widely reported due to the retreat of gully systems, resulting in serious social problems and economic losses. The retreating rate of large gullies has been 0.5–6.6 m/year over the past 2,000 years, estimated by the calculation of erosion modulus, literature archaeology, and field monitoring. The retreating rate of a small gully can reach 7.5–27.0 m/year after a rainstorm. To protect the farmland, buildings, roads, and pipelines near to the gully head areas, a project named Gully Stabilization and Highland Protection (GSHP) was launched by the local government, including the small watershed management (SWM) around loess slopes and gully channels and sponge city construction (SCC) achieved by improving the drainage system of tableland surfaces. These efforts improve the soil and water conservations, although they contribute less to controlling gully expansion. From the perspective of mutual promotion of gravity erosion and hydraulic erosion, this paper proposes a technical framework for GSHP, focusing on the avoidance of geological disaster. This case study reports on an illustrative GSHP project, the restoration of Huoxianggou gully, including the backfilled loess embankment across the gully for convenient urban transportation, and the stabilization of unstable loess slopes. After the implementation, the retreat of the gully head has been stopped, and the soil erosion rate has been reduced by 90%.